PERENCANAAN KOMUNIKASI CORPORATE - Dewi, Yuni Retna (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2009)
Inmany  waysthissubjectisnotaneasy one,since thecorporate communicationsfunction isrelativelynew,certainlytomostEuropean companies.The resourcesputbehindcorporatecommunicationshavenotbeen asgreatasmanyhave feltdesirable,andthecommitmentofthecompany managementhasinmanycasesbeen,atbest,questionable.We areallstill learningthebest  wayofapproachingthisarea,andthetenstepthatwere outlined  above shouldbe taken as guiding stepsrather than a definitive approach.I  havedeliberatelyavoidedreferenceinthischaptertowhatisoften known  as  the  communications  audit.  I  feared   that  to  discuss  the communications auditwouldinmany  ways detractfromthepracticalitiesof planningthecorporatecommunicationsfunction.Theaudit,whichisdescribed elsewhere,isaveryusefulprocesstotakeaccount ofallthecommunications activitiesthatacompanyisengagedin,andassuchitshould  bepartofthe overallcorporatecommunicationsplanningprocess.Indeed,  theapproaches thatIhaveadvocatedareinthemselvessomefromofaudit.Thesuccessorfailureofthecommunicationsplanningprocesswillat thedayrest upon  twokeyfactors: thecommitmentand  energy ofthe top management,andthewillingnessofother individualstosharetheirexperience andexpertisetowardsacommoninterest.Toooften,thesefactorsaresadly missing,because thecorporate  communicationsfunctioneither isnot high enoughonthechairmansagendaor,alternatively,isinconflictwhit theinterest oftheoperatingcompanies.Corporate    communications    planning    requires     determination,                                     commonsensealittlepolitiesandagreatdealofpatience